Tourist Traffic In The Aconcagua Massif Area - Marek, Aneta; Wieczorek, Małgorzata (Quaestiones Geographicae, 2015)
The aim of the article is an analysis of tourist traffic in the Aconcagua massif, one of the most popular peaks of the Seven Summits. On the basis of statistical data, the tourist traffic was analysed in a temporal and spatial perspective. The applied data made it possible to capture the dynamics of visits in the period 2000/2001 – 2012/2013 and with a breakdown into months, which helped analyse the tourist traffic in this area. In each of the analysed periods, January dominates. Data concerning the origin of tourists according to countries and continents, their age, gender and type of mountaineering activity were also taken into account. Most tourists came from Argentina, the USA and Germany. These are people of age groups 21–30 (33%) and 31–40 (31%). Men account for over 75% of visitors. The favourite mountaineering activity is climbing (about 60%). Aconcagua has invariably been a very popular peak among tourists and climbers. It is a place for training and acclimatisation for alpinists, participating in Himalayan expeditions and climbers collecting peaks of the Seven Summits.